The Development of Public Relation Past and Present - Oktri Permata Lani; Ilham, Ilham; Arkaan , Deni; Unel , Temy (Journal International Dakwah and Communication, 2022)
The development of public relations in Indonesia began in 1950 and is increasingly known as PR or public relations. The development of Public Relations in Indonesia moved to accompany the political and state conditions at that time. The Indonesian government realizes that the public needs to be aware of developments that have occurred since the recognition of Indonesian sovereignty by the Dutch kingdom. Starting from this thought, public relations activities began to be institutionalized under the name of public relations because the activities carried out were mostly for outside the organization. Up to now, Public Relations has been used by local governments, state-owned enterprises, the central government or what is more commonly known as “Humas”.